Patch-clamp detection of macromolecular translocation along nuclear pores - Bustamante J.O.; Varanda W.A. (Brazilian Journal of Medical and Biological Research, 1998)
The present paper reviews the application of patch-clamp principles to the detection and measurement of macromolecular translocation along the nuclear pores. We demonstrate that the tight-seal 'gigaseal' between the pipette tip and the nuclear membrane is possible in the presence of fully operational nuclear pores. We show that the ability to form a gigaseal in nucleus-attached configurations does not mean that only the activity of channels from the outer membrane of the nuclear envelope can be detected. Instead, we show that, in the presence of fully operational nuclear pores, it is likely that the large-conductance ion channel activity recorded derives from the nuclear pores. We conclude the technical section with the suggestion that the best way to demonstrate that the nuclear pores are responsible for ion channel activity is by showing with fluorescence microscopy the nuclear translocation of ions and small molecules and the exclusion of the same from the cisterna enclosed by the two membranes of the envelope. Since transcription factors and mRNAs, two major groups of nuclear macromolecules, use nuclear pores to enter and exit the nucleus and play essential roles in the control of gene activity and expression, this review should be useful to cell and molecular biologists interested in understanding how patch-clamp can be used to quantitate the translocation of such macromolecules into and out of the nucleus